Inhibiting system xC− and glutathione biosynthesis – a potential Achilles' heel in mutant-p53 cancers. (3rd September 2017) - Clemons, Nicholas J.; Liu, David S.; Duong, Cuong P.; Phillips, Wayne A.
ABSTRACT: Effective therapeutic strategies to target mutant tumor protein p53 (TP53, best known as p53) cancers remain an unmet medical need. We found that mutant p53 impairs the function of nuclear factor (erythroid-derived 2)-like 2 (NFE2L2, commonly known as NRF2), suppresses solute carrier family 7 member 11 ( SLC7A11) expression, and diminishes cellular glutamate/cystine exchange. This decreases glutathione biosynthesis, resulting in redox imbalance. Mutant p53 tumors are thus inherently susceptible to further perturbations of the SLC7A11 /glutathione axis.